Pengaruh Kepercayaan Merek Dan Promosi Terhadap Loyalitas Konsumen Melalui Kepuasan Konsumen Pada Pengguna Aplikasi E-Commerce Shopee Di Surabaya - Alifah Rizky Wiyanti; Siti Ning Farida (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to understand the impact of brand trust and promotions on consumer loyalty using consumer satisfaction among users of the Shopee e-commerce application in Surabaya. This research uses a quantitative type of research. Use of purposive sampling technique as a tool to determine the sample. This research used a sample of 100 respondents. The population criteria required for the research are users of the Shopee e-commerce application in people who live in Surabaya and have used and made purchases at least twice on the Shopee application. Distributing Google forms was carried out as a technique for collecting the data needed for this research. The form was then distributed online with the aim that the research could reach people living in Surabaya who of course met the required criteria. This type of research data uses primary data. Primary data was collected directly by distributing questionnaires to respondents. The data was analyzed with Partial Least Square (PLS) using the Smart PLS 3 application. The research results explained that a relevant influence was found between the brand trust and promotion variables on the Shopee consumer satisfaction variable. Apart from that, consumer satisfaction, brand trust and promotions also have an impact on Shopee consumer loyalty. This research also proves that a significant influence was found between the brand trust and promotion variables on the Shopee consumer loyalty variable through consumer satisfaction.